Global status and trends of exosomes in neurodegenerative diseases from 2014 to 2023: a bibliometric and visual analysis - Wu, Hao; Li, Yao-lei; Liu, Pan-miao; Yang, Jian-jun (Frontiers in Aging Neuroscience, 2025)
BackgroundNeurodegenerative diseases (NDs) are chronic and progressive conditions that significantly impact global public health. Recent years have highlighted exosomes as key mechanisms involved in these diseases. This study aims to visualize and analyze the structure and content of exosomes in NDs based on past research to identify new research ideas and directions. Through bibliometric analysis, we assess the current state of research on exosomes in the field of NDs worldwide over the past decade, highlighting significant findings, major research areas, and emerging trends.MethodsPublications on exosomes in NDs research were obtained from the Web of Science Core Collection (WOSCC) database. Eligible literature was analyzed using Bibliometric R, VOSviewer, and Citespace.ResultsBetween 2014 and 2023, 2,393 publications on exosomes in NDs were included in the analysis. The number of relevant publications has been increasing yearly, with China leading in international collaboration, followed by the United States. And China has the largest number of academic scholars as leading and corresponding authors in all the countries, known as the great research society and community. Notable institutions contributing to these publications include Nia, the University of San Francisco California, and Capital Medical University, which rank highly in both publication volume and citations. Dimitrios Kapogiannis is a pivotal figure in the author collaboration network, having produced the highest number of publications (Sato et al., 2011) and amassed 3,921 citations. The journal with the most published articles in this field is The International Journal of Molecular Sciences, which has published 131 articles and received 3,347 citations. A recent analysis of keyword clusters indicates that “Exosome-like liposomes,” “Independent mechanisms,” and “Therapeutic potential” are emerging research hotspots.ConclusionThis is the first bibliometric study to provide a comprehensive summary of the research trends and developments regarding exosomes in NDs studies. Future research in this area may explore the role of mesenchymal stromal cells, microRNAs (miRNAs), and targeted drug delivery systems to further investigate the underlying mechanisms and develop new therapeutics.